A Nonpolynomial Optimal Algorithm for Sequencing Inspectors in a Repeat Inspection System with Rework - Yang, Moon Hee; Cho, Jae Hyung (Mathematical problems in engineering, 2015)
Assuming that two types of inspection errors are nonidentical and that only the items rejected by an inspector are reworked and sent to the next inspection cycle, we formulate a combinatorial optimization problem for simultaneously determining both the minimum frequency of inspection-rework cycles and the optimal sequence of inspectors selected from a set of available inspectors, in order to meet the constraints of the outgoing quality level. Based on the inherent properties from our mathematical model, we provide a nonpolynomial optimal algorithm with a time complexity of O ( 2 m ) .